2010
DOI: 10.1007/s10822-010-9406-9
|View full text |Cite
|
Sign up to set email alerts
|

DFT calculation of four new potential agents muscarinic of bispyridinium type: structure, synthesis, biological activity, hydration, and relations with the potents W84 and DUO-3O

Abstract: Four new potential agents muscarinic (allosteric modulators) were synthesized and studied by using the B3LYP density functional method. The optimum conformation and geometry structure of these compounds were determined and analyzed. Solvent effects were considered including a variable number (1-15) of explicit water molecules surrounding the compound in order to simulate the first hydration shell, as well as using the Tomasi's polarized continuum model (PCM). A similar simultaneous analysis of the potents W84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…B3LYP is slightly better than the M06L method, in accordance to a previous work carried out by us in a benzene derivative [25]. In general, DFT methods have been applied properly in many studies of drug design [26][27][28][29], in canonical nucleosides [30,31] and in nucleosides analogues [32,33]. In particular, the B3LYP/DFT method was chosen mainly because of the following three reasons: (i) this method is one of the most accurate and mostly used today in many biological systems [34,35], including Watson-Crick DNA base mispairs [36][37][38][39], i.e.…”
Section: Methodssupporting
confidence: 76%
“…B3LYP is slightly better than the M06L method, in accordance to a previous work carried out by us in a benzene derivative [25]. In general, DFT methods have been applied properly in many studies of drug design [26][27][28][29], in canonical nucleosides [30,31] and in nucleosides analogues [32,33]. In particular, the B3LYP/DFT method was chosen mainly because of the following three reasons: (i) this method is one of the most accurate and mostly used today in many biological systems [34,35], including Watson-Crick DNA base mispairs [36][37][38][39], i.e.…”
Section: Methodssupporting
confidence: 76%
“…In general, DFT methods appear as the most suitable today because they offer a compromise between the important demands put on computer power and time, and the desired chemical accuracy. Furthermore, these methods have been used satisfactorily in many spectroscopic studies, in nucleosides, DNA base pairs, water cluster of nucleobases, biological molecules, and in drug designing, in particular the M062X method selected here …”
Section: Computational Methodologymentioning
confidence: 99%
“…Different studies have shown that the data obtained with DFT methods are in good agreement with those obtained by expensive computational methods as MP2 [31,32,33,34,35]. Also they give good results in many studies on nucleosides and on drug design [36,37] and they predict vibrational frequencies of DNA bases better than HF and MP2 [38,39,40,41,42]. Moreover, because of the high size of ACV, MP2 calculations were only possible with the 6–31G(d) basis set for memory computer problems.…”
Section: Computational Detailsmentioning
confidence: 85%